2015
DOI: 10.1021/ic502892r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of NHC-Supported Ni2222-S2)-Bridging Disulfide and Ni2(μ-S)2-Bridging Sulfide Complexes

Abstract: The (IPr)Ni scaffold stabilizes low-coordinate, mononuclear and dinuclear complexes with a diverse range of sulfur ligands, including μ(2)-η(2),η(2)-S2, η(2)-S2, μ-S, and μ-SH motifs. The reaction of {(IPr)Ni}2(μ-Cl)2 (1, IPr = 1,3-bis(2,6-diisopropylphenyl)imidazolin-2-ylidene) with S8 yields the bridging disulfide species {(IPr)ClNi}2(μ(2)-η(2),η(2)-S2) (2). Complex 2 reacts with 2 equiv of AdNC (Ad = adamantyl) to yield a 1:1 mixture of the terminal disulfide compound (IPr)(AdNC)Ni(η(2)-S2) (3a) and trans-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 79 publications
4
26
0
Order By: Relevance
“…The solid‐state structures of 32 and 33 feature Y‐shaped coordination environments at Ni (Figure ). Surprisingly, the Ni–S distances in 32 (2.064(2) Å) and 33 (2.084(1) Å) are comparable to those observed for a variety of Ni 2 (µ‐S)‐type complexes (Table ),, , suggesting that the π‐bonds in 32 and 33 are no stronger than those of bridging sulfides. In addition, both 32 and 33 feature interactions (albeit weak) between the sulfide ligand and the potassium counterion, despite the use of either 18‐crown‐6 or 2.2.2‐cryptand to sequester the K + ion.…”
Section: Synthesis and Structure Of M=s Complexesmentioning
confidence: 57%
See 2 more Smart Citations
“…The solid‐state structures of 32 and 33 feature Y‐shaped coordination environments at Ni (Figure ). Surprisingly, the Ni–S distances in 32 (2.064(2) Å) and 33 (2.084(1) Å) are comparable to those observed for a variety of Ni 2 (µ‐S)‐type complexes (Table ),, , suggesting that the π‐bonds in 32 and 33 are no stronger than those of bridging sulfides. In addition, both 32 and 33 feature interactions (albeit weak) between the sulfide ligand and the potassium counterion, despite the use of either 18‐crown‐6 or 2.2.2‐cryptand to sequester the K + ion.…”
Section: Synthesis and Structure Of M=s Complexesmentioning
confidence: 57%
“…For example, reaction of excess S 8 with [Co(PMe 3 ) 4 ] results in formation of the bridging sulfide complex, [(PMe 3 ) 3 Co] 2 (µ‐S) 2 , in excellent yields, along with Me 3 PS, but not a terminal sulfide . This result is typical of elemental sulfur additions to the late metals . Similary, Sacconi and co‐workers reported that deprotonation of [(np 3 )Co(SH)][BPh 4 ] ( 17 , np 3 = tris(2‐diphenylphosphinoethyl)amine) with NaOEt also resulted in formation of a Co I bridged sulfide, [(np 3 )Co] 2 (µ‐S) ( 18 ), according to the stoichiometry shown in Scheme a .…”
Section: Synthesis and Structure Of M=s Complexesmentioning
confidence: 84%
See 1 more Smart Citation
“…Tatsumi et al reported that substitution of the bridging halide ligands with sulfide anions resulted in efficient formation of the corresponding μ-sulfide Ni(I) dimer 16a [ 47 ]. Olechnowicz et al also synthesized the NHC analogue 16b , in which the bridging thiolate was μ–SH, from Sigman’s dimer [ 48 ]. Interestingly, this complex was also obtained from the heterolytic cleavage of H 2 in the presence of the sulfido-bridged Ni(II) dimer [Ni(IPr)(μ-S)] 2 [ 49 ].…”
Section: Preparation Structure and Properties Of Dinuclear Nickementioning
confidence: 99%
“…[29][30][31]34] TheN i ÀSb ond lengths in complexes 3, 4,a nd 5 are amongst the shortest known, and are intermediate between the additive covalent radii projected for nickel-sulfur single (2.13 ) and double bonds (1.95 ). [23,24,35] Forc omparison, [{L tBu Ni} 2 (m-S)], [30] [{(IPr)Ni} 2 (m-S) 2 ]( IPr = 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene), [36] and [{PhB-(CH 2 StBu) 3 }Ni] 2 (m-S) [32] display comparable NiÀSb ond lengths of 2.0651(7), 2.0972(6), and 2.0714(4) , respectively, despite each possessing ab ridging S 2À ligand. Overall, this suggests similar magnitudes of p-bonding in both classes of materials.…”
mentioning
confidence: 99%